2016
DOI: 10.4172/2165-7920.1000910
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Surgical Treatment of Undiagnosed Placenta Percreta

Abstract: Background: To describe a case of a 38-year old pregnant woman with an intraoperative diagnosis of placenta percreta complicated by central placenta previa. The ultrasound scan did not show signs of any type of abnormal placental invasion, just central placenta previa was visualized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The only one (2.04%) case was maternal death in our study after Caesarian Hysterectomy in the second day post-operative due to cardiac asystole and this less than figures reported by Guleria et al [10]In a national study in the United States, however, a mortality rate of 1.0% was recorded in women who underwent obstetric hysterectomy [84], and this is consistent with our study. .Our results demonstrated that postnatal hospital stay duration in the caesarian hysterectomy group was 5days.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The only one (2.04%) case was maternal death in our study after Caesarian Hysterectomy in the second day post-operative due to cardiac asystole and this less than figures reported by Guleria et al [10]In a national study in the United States, however, a mortality rate of 1.0% was recorded in women who underwent obstetric hysterectomy [84], and this is consistent with our study. .Our results demonstrated that postnatal hospital stay duration in the caesarian hysterectomy group was 5days.…”
Section: Discussionsupporting
confidence: 92%
“…[12]So maternal morbidity rate of 9.5%. [10]A maternal mortality rate of 7 -10% has been quoted by a number of reviews, which is alarmingly high. [13,14,5,15,16,17] The most recent confidential inquiry into maternal mortality in the United Kingdom (MMBRACE-UK, 2017) highlighted the continued high maternal mortality associated with the condition.…”
Section: Introductionmentioning
confidence: 99%